(untitled) (Mustansiria Dental Journal, 2023)
Aim: The purpose of this research was to compare the fracture resistance of obturated roots prepared by using the Race Evo, Edge File X7, and Protaper Gold file systems. Materials and methods: 60 extracted maxillary first molars were selected, their coronal portions were removed and their working length was calculated. The samples were separated into three experimental groups according to the used NiTi rotary systems and one control group; each group contains 15 samples. Group one remained uninstrumented (control), Groups 2-4 were instrumented by the Race Evo (FKG Dentaire SA, La Chaux-de-Fonds, Switzerland), Edge File X7(Edge Endo; Albuquerque, New Mexico, United States), and Protaper Gold file systems (Dentsply, Maillefer, Switzerland) respectively. After instrumentation, the experimental groups were filled using a single-cone technique. The sealer was mixed according to manufacturing instructions with master Gutta-Percha cones of size 40 (0.04 taper, (Diadent Group International, Korea) for Race Evo and Edge file X7, and size 40 taper 0.06 for the Protaper Gold file system (Dentsply, Maillefer, Switzerland). To set the sealer, the specimens were kept at 37 °C and 100% humidity for two weeks. The root fracture stress was measured in Newtons using Instron universal testing equipment. Results: One Way ANOVA test showed there was a significant difference in the mean value of the fracture resistance between the four groups (P < 0.05). The LSD test was used for the comparison of the multiple groups so the control group showed the highest fracture resistance among groups (p < 0.05). among the experimental groups, the roots prepared by Race Evo showed the highest fracture resistance (p < 0.05), while roots prepared by Protaper Gold and Edge file x7 showed the lowest fracture resistance with a statistically significant difference (p > 0.05)